Isolation and characterization of Pb- and Cr-tolerant phosphate-solubilizing bacteria and optimization of culture conditions - Jiang, Huanhuan; Chen, Lu; Zeng, ShiYao; Xu, Xiangping; Zhang, Jieying; Liang, MinHua; Zhang, Jiamin; Liang, Shengnian; Ji, Qianhua (Frontiers in Microbiology, 2026)
IntroductionPhosphate-solubilizing bacteria (PSB) that tolerate heavy metals may enhance phosphorus availability in contaminated soils and provide candidates for bio-based management.MethodsPSB were isolated from farmland rhizosphere soil and screened on tricalcium phosphate medium. Soluble phosphorus (soluble P) was quantified in liquid culture using tricalcium phosphate, ferric phosphate, aluminum phosphate, and lecithin as insoluble phosphorus (insoluble P) sources. Pb/Cr tolerance was assessed by growth on metal-amended plates and minimum inhibitory concentration (MIC) assays, and six dominant isolates were identified by 16S rRNA gene sequencing.ResultsEighteen PSB isolates were obtained. All strains solubilized tricalcium phosphate (2.82253.53 mg L-1) and ferric phosphate (6.24206.48 mg L-1); most also solubilized aluminum phosphate (13.0244.73 mg L-1), and 13 isolates solubilized lecithin (2.8230.84 mg L-1). The six strains able to grow at 6 mmol L-1 Pb or Cr were identified as Bacillus sp. (HY-1, HY-6), Bacillus subtilis (HY-3, HY-16), Bacillus thuringiensis (HY-12), and Duganella sp. (HY-13). MICs were higher for Cr (1720 mmol L-1) than for Pb (67 mmol L-1), and increasing Pb or Cr suppressed both growth (OD600) and phosphate solubilization. Single-factor optimization identified glucose as the most suitable carbon source and 0.3 g L-1 NaCl as optimal; the best initial pH was 6 for five strains (pH 7 for HY-12), and temperature optima were strain-dependent (3040 °C).ConclusionThese results define cultivation parameters for inoculum preparation and support further testing in soil and plant systems under environmentally relevant conditions.